Innovation in Islamic Religious Education for Elementary School Students by Empowering Sophisticated Digital Resources - Munawati, Siti (Universitas Pendidikan Indonesia, 2024)
Modern religious education faces difficult challenges caused by rapid technological advances and changes in the socio-cultural environment. One of its main tasks is to improve the quality of religious education and ensure the effectiveness of religious learning in elementary schools. The dissemination of knowledge through technology is an urgent matter but it is also necessary to develop competencies and adapt to today's world. The aim of the research is to analyze and improve the methodological competence of educators by using digital educational resources for religious education. The research method used was empirical with a total of 360 respondents. Data collection techniques include observation, interviews and surveys, monitoring student learning activities, studying teacher experiences, conducting practical-experimental discussions, and surveys, as well as analyzing and evaluating student work results. Analysis techniques include methodological reflection, critical evaluation, quality revision, and analysis of methods and exercises used in terms of suitability and effectiveness. As a result, digital educational resources were found to be an effective method in forming the professional orientation of future religious educators. These findings encourage the professional training of future educators and to improve professional qualifications in basic education institutions. In conclusion, the importance of integrating digital technology into the educational process to improve the quality of education and develop student competencies.